2014
DOI: 10.1089/acm.2013.0204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Transcendental Meditation Technique on Trait Anxiety: A Meta-Analysis of Randomized Controlled Trials

Abstract: Overall, TM practice is more effective than treatment as usual and most alternative treatments, with greatest effects observed in individuals with high anxiety. More research is needed in this area, especially with high-anxiety patients, conducted under medically supervised conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 37 publications
3
75
1
3
Order By: Relevance
“…Practice of TM primarily increases EEG alpha-coherence and synchrony, especially in the prefrontal cortex, and is associated with deep relaxation and improved executive functioning. 27 Metaanalyses have found that the TM technique was more effective than other meditation and relaxation techniques for reducing trait anxiety. 28 Participants were encouraged to practice their meditation program individually in their prison cells, sitting with eyes …”
Section: Transcendental Meditation Programmentioning
confidence: 99%
“…Practice of TM primarily increases EEG alpha-coherence and synchrony, especially in the prefrontal cortex, and is associated with deep relaxation and improved executive functioning. 27 Metaanalyses have found that the TM technique was more effective than other meditation and relaxation techniques for reducing trait anxiety. 28 Participants were encouraged to practice their meditation program individually in their prison cells, sitting with eyes …”
Section: Transcendental Meditation Programmentioning
confidence: 99%
“…In addition, stress can adversely affect a range of health conditions, including both mental health and cardiovascular outcomes. 4 Meditation instruction has been shown in multiple previous studies to favorably modify physiologic indicators of stress and to improve clinical outcomes for patients with anxiety, 5 posttraumatic stress disorder, 6 substance use disorders, 7 and cardiovascular disease.…”
Section: Two Papersmentioning
confidence: 99%
“…During 2006-2009 out of 33,045 physician office visits, stress management counseling was the least common type of counseling accounting for only 3% of the patients. Research has shown that stress can negatively affect health but cardio-respiratory synchronization via alternate nostril breathing techniques such as Pranayama [107,61] and meditation practice can help attenuate some of these symptoms associated with stress-related disorders and anxiety [108][109][110] due to the shift from a sympathetic state to a parasympathetic state [56,111].…”
Section: Clinical Applications Arising From Our Understanding Of the mentioning
confidence: 99%